Critical dimensions of trans‐sacral corridors assessed by 3D CT models: Relevance for implant positioning in fractures of the sacrum. Issue 11 (13th March 2017) - Wagner, Daniel; Kamer, Lukas; Sawaguchi, Takeshi; Geoff Richards, R.; Noser, Hansrudi; Uesugi, Masafumi; Ossendorf, Christian; Rommens, Pol M.
ABSTRACT: Trans‐sacral implants can be used alternatively to sacro‐iliac screws in the treatment of osteoporosis‐associated fragility fractures of the pelvis and the sacrum. We investigated trans‐sacral corridor dimensions, the number of individuals amenable to trans‐sacral fixation, as well as the osseous boundaries and shape of the S1 corridor. 3D models were reconstructed from pelvic CT scans from 92 Europeans and 64 Japanese. A corridor of <12 mm was considered critical for trans‐sacral implant positioning, and <8 mm as impossible. A statistical model of trans‐sacral corridor S1 was computed. The limiting cranio‐caudal diameter was 11.6 mm (±5.4) for S1 and 14 mm (±2.4) for S2. Trans‐sacral implant positioning was critical in 52% of cases for S1, and in 21% for S2. The S1 corridor was impossible in 26%, with no impossible corridor in S2. Antero‐superiorly, the S1 corridor was limited not only by the sacrum but in 40% by the iliac fossa. The statistical model demonstrated a consistent oval shape of the trans‐section of corridor S1. Considering the variable in size and shape of trans‐sacral corridors in S1, a thorough anatomical knowledge and preoperative planning are mandatory using trans‐sacral implants. In critical cases, S2 is a veritable alternative. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:2577–2584, 2017. Abstract : The complex and variable anatomy of the upper sacrum as well as the iliac fossa limits the use of trans‐sacral implants. Trans‐sacral implant positioning was critical in 52% of cases for S1, and in 21% for S2. The S1 corridor was impossible in 26%, with no impossible corridor in S2. Despite a consistent oval shape of the S1 corridor, this underlines the importance of a thorough preoperative planning when using these implants.